Detecting brain tumor using deep neural networks from MRI images - Imamuzzaman, A.S.M.; Sakline, Redwan Islam; Junaed, Sayed Rafi; Hossain, Mohammad Iqbal; Das, Dipto (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.